Severidad del daño causado por los incendios forestales en los bosques remanentes de Nothofagus alessandrii Espinosa en la Región del Maule de Chile - VALENCIA, DIEGO; SAAVEDRA, JORGE; BRULL, JORDI; SANTELICES, RÓMULO (Gayana Botánica, 2018)
A forest fire in 2017 consumed about 184,000 hectares among which an important part of Nothofagus alessandrii forests, which is also an endangered species, was affected. Sentinel II images and the Normalized Burn Ratio (dNBR) indices were used to evaluate the fire severity on N. alessandrii forests. Results show that 172 hectares were affected by the fire (55 % of the known remaining forests). High severity and Moderate-high severity burn surface was 89 hectares (28 % of the total burned) and this would be the most difficult area to be recovered by the system.